(untitled) (Research, Society and Development, 2022)
The HMB’s main function is to provide assistance to children’s health in the country. than 1.1 million Brazilian women. Objective: to identify the effective communication of the multidisciplinary team in the Human Milk Bank (HMB) to promote breastfeeding. Methodology: The methodological strategy of action research used for development, through an exploratory study, supported by the term transversal orality, with a quanti-quali approach. Participated in the study 19 professionals who make up the multidisciplinary team of the Human Milk Bank (BLH) - Dr. João Aprígio – from the Santa Casa de Misericórdia do Pará Foundation – FSCMP. Results: the construction of a strategy that favors effective communication between users and professionals of the Human Milk Bank (BLH)- Dr. João Aprígio – from Fundação Santa Casa de Misericórdia do Pará - FSCMP, a tool capable of promoting breastfeeding and mobilizing society to support women’s demands. Conclusion: It is suggested, in order to have a future perspective, to present a technical opinion for middle management as a suggestion of strategies for the execution and implementation of a tool capable of favoring effective communication between users and the multidisciplinary team of a highly complex service. In addition, present a proposal for the creation and validation of an accessible and practical mobile application based on a real diagnosis.